Calculation of Axial Compression Capacity for Square Columns Strengthened with HPFL and BSP - Hua Huang; Kailin Xi; Yu Zhang; Jinghui Shi; Boquan Liu (Advances in Materials Science and Engineering)
The load carrying capacity and failure mechanism of 8 square columns strengthened with high-performance ferrocement laminate (HPFL) and bonded steel plates (BSP) were analyzed on the basis of experiments on the axial compression performance of these columns. Results show that the reinforcing layer worked together with the original columns as a whole, and the load-bearing capacity significantly increased. When failure of the strengthened column occurred, the mortar and concrete were crushed and bulged outward in the middle of the columns, the angle bars and longitudinal steel bars buckled, and some stirrups were pulled out. The chamfering of angle bar momentously affected the primary damage of steel strand. The values of the strength reduction factor and pressure effective utilization coefficient of the mortar were suggested. Based on the experiments and existing tests of 35 columns strengthened with HPFL, equations for the axial compression bearing capacity were proposed and all calculation results agreed well with testing results. Therefore, the calculation method could be used in the capacity design of axial compression strengthened columns.